Dlhodobé výsledky liečby zlomenín diafýzy femuru u detí - Omaník, Pavol; Sýkora, Ľubomír; Kozlíková, Katarína; Béder, Igor; Murár, Erich; Horn, František (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2009)
PURPOSE OF THE STUDY Bone overgrowth of the femur after fracture in childhood treated either conservatively or surgically is well documented. The aim of this study was to investigate the frequency of bone overgrowth in childhood fractures treated by elastic stable intramedullary nailing (ESIN), to evaluate it in relation to conservative treatment and to compare its presence in the youngest age categories. MATERIAL AND METHODS A total of 49 patients, age range 4 to 17 years, with femoral shaft fracture treated in our department by ESIN osteosynthesis between 2001 and 2005 were asked to appear for a follow-up not earlier than one year after the fracture had healed to be examined for the presence of bone overgrowth. The results were statistically analysed and compared with agroup of 99 patients treated conservatively (CONS) between 1987 and 1997. RESULTS In the ESIN group, femoral overgrowth ranging from 5 to 22 mm was found in 15 out of 49 patients. It was most frequent in children up to 6 years of age; with an increasing age overgrowth frequency decreased. In the CONS group, overgrowth was recorded in 30 out of 99 patients and ranged from 4 to 20 mm. Similarly to the ESIN group, it was most frequent in the youngest age category (up to 6 years). In relation to age categories, there were no significant differences in overgrowth values between surgical and conservative treatment. DISCUSSION ESIN osteosynthesis is currently the most universal method of surgical treatment for long-bone fracture. Although it has undisputable benefits, it may also be associated with longitudinal femoral overgrowth. Children in youngest age categories are often not indicated for ESIN for the fear of bone overgrowth. CONCLUSIONS The use of ESIN for treatment of femoral fractures in childhood is not associated with a higher risk of long-bone overgrowth, as compared with conservative therapy. Moreover, the authors? experience shows that the method of retrograde insertion of osteosynthetic material is safe even in distal diaphyseal fractures and does not increase risk of bone overgrowth.
Keywords: diafýzy; Humans; Femoral Fractures; dítě; Fracture Healing; Child; Female; intramedulární fixace fraktury; lidé; hojení fraktur; fraktury femuru; femur; předškolní dítě; Femur; ženské pohlaví; Male; Adolescent; Diaphyses; mužské pohlaví; Child, Preschool; Fracture Fixation, Intramedullary; mladiství